DOWNWARD SPIRAL IN CIVIL SERVICE ANONYMITY AND NEUTRALITY: AN ANALYSIS OF INDIAN BUREAUCRACY DURING RISE OF CHAUVINISM AND RIGHT-WING NATIONALISM - Naseer Ahmad Bhat, Bazila Shameem, Nisha Yadav (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Civil service neutrality and anonymity flows from the Whitehall model which reverberates in Westminster administrative traditions of UK, Australia, New Zeeland and Canada. This model depicts that Public servants/bureaucrats should be politically neutral and work ‘behind the curtains’ remaining aloof from din and fury of being recognized publicly or appreciated for that matter. Permanency of bureaucracy vis-à-vis political executive makes the cardinal principles of neutrality and anonymity a sine qua non. Advent of Social media has raised a question mark over these two principles. The case of Indian civil services is no different. This article analyses the dwindling of core principles of Anonymity and Neutrality in the context of growing Right-Wing Nationalism and Chauvinism in India. Further this article analysis the social media handles of various top-level bureaucrats (including ex-ones) who are at the helm of important portfolios (both civil and police) and have used their social media handles particularly twitter to knell a death blow to two cardinal principles of Civil Service Neutrality and Anonymity.